(untitled) (Fourth World Journal, 2025)
In broad strokes this study traces the history of capitalism’s merge with Fourth World nations in the United States as a tool of settler colonialism and as a “case study” for capitalism’s infiltration of all Fourth World peoples. As a subordinate process to colonialism, capitalism was deployed in service to settler colonialism’s imperative to eliminate Fourth World peoples. At the same time, paradoxically, Fourth World nations in the United States have endured, and can be seen to be in a process of ongoing political development. Four examples of changing modes of political economy are considered as a demonstration of agency and Fourth World peoples’ ability to adapt to changing political and economic circumstances, while disrupting narratives of native savagery and romanticized depictions of Fourth World peoples as always “pure,” “authentic,” and unchanging. The essay then examines the history of federal Indian policy from the Progressive Era forward, identifying the economic imperatives at the root of each twentieth century policy. While many complex processes are involved, including ideological commitments to Social Darwinism and progressive reformers’ commitments to improve indigenous lives by bestowing upon them civilization, these processes can be seen to be mediated by imposed economic conformity to the capitalist state, even in the current moment of self-determination. Fourth World nations’ decolonization projects, however, reveal certain tensions between the concept of settler colonialism and Fourth World political development.